Microbial community structure along an altitude gradient in three different localities - Ma, Xiaojun; Chen, Tuo; Zhang, Gaosen; Wang, Rui (Folia microbiologica, 2004)
The microbial community structure along an altitude gradient was investigated in different localities, in Kalasi lake, Urumqi river and Sangong river, Xingjiang (China). The mean numbers of DAPI (4',6-diamidino-2-phenylindole)-stained cells were lower in Kalasi lake than that in Urumqi river and Sangong river; these differences were attributed to increasing environmental harshness including lower soil organic carbon and nitrogen content, more acidic pH and lower annual temperature. In each locality, the numbers of bacteria and archaea measured with two fluorescence-labeled 16S rRNA oligonucleotide probes (EUB338 and ARCH915) were higher in a coniferous forest and lower in desert vegetation. A significant and positive relationship was found between microbial and soil organic carbon and total nitrogen along the altitudinal gradient, indicating that plant communities and soil nutrients influence the soil microbial structure. The results show that the microbial population in higher latitudinal site was fewer than lower latitudinal one, soil microorganisms were positively correlated to soil organic carbon and total nitrogen, and plant communities had an obviously impact on soil microbes.
Keywords: indoly; geny rRNA; Nitrogen; DNA, Ribosomal; dusík; Indoles; Temperature; Ecosystem; Čína; Genes, Bacterial; Genes, rRNA; teplota; RNA ribozomální 16S; Archaea; Soil Microbiology; China; Colony Count, Microbial; RNA, Ribosomal, 16S; barvení a značení; nadmořská výška; Carbon; archeální geny; Altitude; bakteriální geny; půdní mikrobiologie; počet mikrobiálních kolonií; Hydrogen-Ion Concentration; geologické sedimenty; ribozomální DNA; Bacteria; uhlík; koncentrace vodíkových iontů; Genes, Archaeal; Staining and Labeling; Geologic Sediments; ekosystém